Lateral pharyngotomy extended by resection of the mandibular angle-an alternative approach to the surgical treatment of oropharyngeal (tonsillar) cancers - Cocek, Ales; Průcha, Ivan; Hahn, Ales (Acta oto-laryngologica, 2009)
CONCLUSION: The authors found the procedure, when used with the proper indications, to be an uncomplicated and expeditious method that presents little risk to surrounding structures, has no residual cosmetic or functional consequences for the patient, presents a low risk of complications, and has a good oncological outcome. The main indications for this procedure are related to the extent of the tumour and the surgeon's experience with the method. OBJECTIVES: This study assessed the radical extent of each surgery, which was determined histopathologically, local and general complications to determine the safety of the procedure, and oncological and post-operative efficacy. METHOD: In the 1970s, Tichy described, in Czech literature, an approach to treating oropharyngeal tumours through a lateral pharyngotomy with the approach extended by resection of the mandibular angle. From 2000 to 2006 the authors use this method to treat 63 patients having oropharyngeal cancer in various stages (T1 19%, T2 46%, T3 14%, T4 21%). RESULTS: Microscopically, the operation was non-radical in three cases (4.8%). Of the local complications encountered, pharyngocutaneous fistulas were the most frequent, three cases (4.8%), and postoperative bleeding was seen in two cases (3.2%). General complications were seen in four cases (6.4%).
Keywords: lidé středního věku; pooperační komplikace; Radiotherapy, Adjuvant; Male; dospělí; Mandible; Postoperative Complications; lidé; senioři; Aged; Oropharyngeal Neoplasms; adjuvantní radioterapie; farynx; ženské pohlaví; mandibula; spinocelulární karcinom; Adult; mužské pohlaví; nádory orofaryngu; Pharynx; Middle Aged; Humans; Carcinoma, Squamous Cell; Female